2017
DOI: 10.1590/1807-1929/agriambi.v21n9p657-662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different conductor tubes on the longitudinal distribution of corn seeds

Abstract: A B S T R A C TThe correct longitudinal distribution of seeds by the seeder machine is one of the features that most contributes to obtain an adequate plant stand and good crop yield. The objective of this study was to evaluate the longitudinal distribution of corn seeds by seed conductor tube types, combined with a horizontal perforated disc and a pneumatic meter, altering the seeding density rate. The experiment was conducted in a laboratory using a seed meter test bench. Treatments were a combination of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
1
10
0
6
Order By: Relevance
“…Corn seed distribution was more homogeneous (precision index) in the curved seed tube at all simulated speeds (Figure 4e). Carpes et al (2017) reported better efficiencies for corn seed distribution using the curved seed tube due to a reduction in the seed fall speed promoted by the parabolic profile of the tube, promoting smoother seed flowability to the furrow.…”
Section: Distribution Of Corn Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…Corn seed distribution was more homogeneous (precision index) in the curved seed tube at all simulated speeds (Figure 4e). Carpes et al (2017) reported better efficiencies for corn seed distribution using the curved seed tube due to a reduction in the seed fall speed promoted by the parabolic profile of the tube, promoting smoother seed flowability to the furrow.…”
Section: Distribution Of Corn Seedsmentioning
confidence: 99%
“…The effect of the construction shape of the seed tube stands out among the factors that influence the longitudinal distribution of seeds, varying the length, angle, and diameter of inlet and outlet (Carpes et al, 2017), in addition to the sowing speed of the seed drill (Nadin et al, 2019). This study aimed to evaluate the influence of the seed tube curvature on the longitudinal distribution of corn and soybean seeds at different sowing speeds.…”
Section: Introductionmentioning
confidence: 99%
“…A utilizada por Reis et al (2007) é estruturada em coluna tubular metálica única, com uma base estabilizadora inferior fixa. A utilizada por Carpes et al (2017), está configurada em uma estrutura metálica de forma retangular, utiliza uma esteira para o recolhimento e posterior contagem de sementes e análise de espaçamentos. Já a bancada de ensaios desenvolvida neste trabalho usará um 5 3 2 1 8 7 4 6 sensor ótico posicionado na saída da semente do dosador para esse fim.…”
Section: Descriçãounclassified
“…A ABNT (1996) estabelece, no projeto de norma (04:015.06-004/1996) para semeadoras de precisão, dentre outros, métodos de ensaios em laboratório para a avaliação da regularidade de distribuição longitudinal de sementes. Carpes et al (2017), avaliaram a distribuição longitudinal de sementes de milho por diferentes tipos de tubos condutores, variando a densidade de semeadura, e para isso, utilizaram um dosador de disco horizontal e um dosador pneumático. O experimento foi conduzido em laboratório utilizando uma bancada de ensaio de dosadores de sementes.…”
Section: Introductionunclassified
“…Similar to the title of this paper, many authors are investigating seed distribution with different types sowing machines [15][16][17][18]. Also, the main problem of sowing is to determine longitudinal, lateral and depth seed distribution [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%